Adolescentna medicina: 1. in 2. modul - Mičetič Turk, Dušanka; Vogrin, Bernarda (2023)
Adolescet Medicine: l. and 2. Module. Adolescence is a period of turbulent bio-psycho-social development. Far this reason, adolescents and young adults are particularly vulnerable groups, to whom the health profession must pay special attention. The lnternational Union of Medica! Specialists (UEMS) has adopted the position that every medica! specialist who works with adolescents and young adults (10-24 years) must acquire basic knowledge of adolescent medicine that addresses the main peculiarities of development in adolescence and the resulting specific health problems needs. They also recommend that contents from adolescent medicine be included in all specializations that are in contact with adolescents and young adults. Until now, in Slovenia, we have had no systematic education in the field of adolescent medicine. The Faculty of Medicine in Maribor recognized the need for this type of education. With the establishment of the Institute for Adolescent Medicine and Preventive Pediatrics, the basic conditions for the development of the profession at the undergraduate and postgraduate level from an educational and research point of view are provided. Within the framework of the institute, we designed a postgraduate education plan in adolescent medicine, which is intended for specialists and specialists in pediatrics, family medicine, surgery and interna! medicine, as well as all other doctors who would like to acquire additional knowledge in adolescent medicine. The program is designed based on the recommendations of the UEMS and the program of the European School of Adolescent Medicine (Euteach, Lausanne, Switzerland and guidelines of the World Health Organization (WHO) (3-5). The education ta kes place in four two-day modules.
Keywords: adolescent medicine; education; lectures; workshops; proceedings